2013
DOI: 10.1002/car.2280
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Child Sexual Abuse: Delays, Non‐disclosure and Partial Disclosure. What the Research Tells Us and Implications for Practice

Abstract: This paper reviews the research on disclosure of child sexual abuse with specific reference to delays in disclosing, non‐disclosure and partial disclosure of experiences of child sexual abuse. Findings from large‐scale national probability studies highlight the prevalence of both non‐disclosure and delays in disclosure, while findings from small‐scale qualitative studies portray the complexity, diversity and individuality of experiences. The possible explanations regarding why children are reluctant to disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(193 citation statements)
references
References 32 publications
7
160
0
10
Order By: Relevance
“…Several authors suggest that CSA is a particularly stigmatized form of maltreatment with different accompanying barriers of disclosure, especially for boys (Ungar et al, 2009). Past studies have found that men are less likely to disclose sexual abuse (Hébert et al, 2009;McElvaney, 2015). The vast majority of sexual abuse cases involve male perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggest that CSA is a particularly stigmatized form of maltreatment with different accompanying barriers of disclosure, especially for boys (Ungar et al, 2009). Past studies have found that men are less likely to disclose sexual abuse (Hébert et al, 2009;McElvaney, 2015). The vast majority of sexual abuse cases involve male perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos autores (Collin-Vézina et al, 2015;Goodman-Browne et al, 2003;Hershkowitz et al, 2005;Kogan, 2004;Lam, 2014;Leclerc & Wortley, 2015;McElvaney, 2015;Paine & Hansen, 2002) han señalado que existe una serie de factores que influenciarían el proceso de develación, lo que llevaría a un retraso de esta e, inclusive, a no develar. Específicamente, se han estudiado características del contexto de la agresión, tales como severidad y cronicidad, estrategias de victimización y la relación con el agresor; características individuales de las víctimas, tales como la motivación por develar, la edad y el género; y características del ambiente del niño, tales como la reacción familiar y la credibilidad familiar y materna.…”
Section: Factores Asociados Al Proceso De Develaciónunclassified
“…Las investigaciones dan cuenta de que los niños víctimas de ASI a menudo no develan (incluso ante preguntas o cuando puedan haber otros signos, como físicos) o presentan importantes demoras en la develación e, inclusive, muchas personas no comunican el contenido de la agresión hasta la edad adulta o solo al ser preguntados en el marco de los estudios (Alaggia, 2004;Baía, Veloso, Magalhães & Dell'Aglio, 2013;Goodman-Brown, Edelstein, Goodman, Jones & Gordon, 2003;McElvaney, 2015;Schaeffer, Leventhal & Asnes, 2011). Por ejemplo, en el estudio de Priebe y Svedin (2008) con población general adolescente un 18,6% de las mujeres y un 30,9% de los hombres que reportan haber vivido experiencias de abuso sexual nunca había develado la experiencia de ASI vivida previo al estudio y solo un 6,8% lo había reportado a la policía o autoridades.…”
unclassified
See 2 more Smart Citations